PENGARUH KEMUDAHAN PENGGUNAAN DAN PERSEPSI RISIKO TERHADAP LOYALITAS PENGGUNA APLIKASI INVESTASI REKSADANA ONLINE DENGAN KEPUASAN PENGGUNA SEBAGAI VARIABEL MEDIASI PADA MAHASISWA UNIVERSITAS PALANGKA RAYA - Pebri Rahman; Muhammad Afrizal; Solikah Nurwati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze the influence of perceived ease of use and perceived risk on the loyalty of online mutual fund investment application users, with user satisfaction as a mediating variable among students of Universitas Palangka Raya. This study uses a quantitative approach with a survey method involving 201 respondents selected through purposive sampling and proportionate stratified random sampling techniques. Data are collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that perceived ease of use has a positive and significant effect on user satisfaction (p = 0.000). Perceived risk also has a positive and significant effect on user satisfaction (p = 0.012). Furthermore, perceived risk has a positive and significant effect on user loyalty (p = 0.006), while user satisfaction has a positive and significant effect on user loyalty (p = 0.009). However, perceived ease of use does not have a significant direct effect on user loyalty (p = 0.614). The mediation analysis shows that user satisfaction mediates the effect of perceived ease of use on user loyalty, but does not mediate the relationship between perceived risk and user loyalty. These findings indicate that user satisfaction plays an important role in building user loyalty toward online mutual fund investment applications. Therefore, service providers need to improve ease of use, system security, and service quality to enhance user satisfaction and maintain user loyalty.